Prinsip Deklaratif Sebagai Wujud Perlindungan Hukum Bagi Pemegang Hak Cipta Atas Ciptaan Sketsa Tugu Selamat Datang di Jakarta : Studi Kasus Putusan Nomor 35/Pdt.Sus-Hak Cipta/2020/PN Niaga Jkt.Ps - Wibowo, Sigit (Jurnal Hukum Caraka Justitia, 2024)
The research aims to determine and analyze the resolution of copyright holder disputes over creative works of sketches of the welcome monument in Jakarta based on declarative principles based on Indonesian positive law. The research method uses normative juridical research. This type of research is intended as a type of dogmatic (doctrinal) research and a form of descriptive research about laws. The approach to this research is a statutory approach and a case approach related to the application of the declarative principle for the copyright holder of a creative work, Sketsa Tugu Selamat Datang, against other parties who use the sketch's copyrighted work, without the permission of the copyright holder, such as in cases of copyright infringement. sketch of the welcome monument registered in case Decision Number: 35/Pdt.Sus-Hak Copyright/2020/PN Niaga Jkt.Ps).The results of this research are a form of legal protection for copyright holders for the Selamat Datang Monument Sketch, namely that the copyright holder has received automatic rights protection (declarative principle) if a work has been created or realized, and has received recognition from the state even though the work has not been registered or published. As well as providing legal protection for moral rights, economic rights (royalties), and rights related to copyright holders. These aspects have characteristics that must be carried out to be fulfilled in law enforcement. Another form of legal protection is a judge's decision that punishes PT. Grand Indonesia (defendant) to pay for material losses suffered by Seana Meaya Nunjung and other heirs (plaintiffs) due to the use of the PT Logo. Grand Indonesia, which is paid in full and at once after the verdict in this case, has permanent legal force.